Letter of Credit Disputes from an Arbitration Perspective - Zaid Aladwan (Hasanuddin Law Review, 2020)
In a recent study, it might not be possible to refer letter of credit fraud cases to arbitration instead of litigation. Alavi’s research suggested that there could be some obstacles, such as obtaining banks’ response and cooperation; the different and high standards of proof of fraud required; and the difficulty in obtaining an injunction. His study answered a question proposed by Blodgett and Mayer as to whether arbitration would ever take place in letter of credit disputes.  This short research paper will answer this question, but from a different angle: whether arbitration will provide more appropriate judgments (award) than litigation regarding letter of credit disputes. This question arises from the writer’s observation that, in the past twenty years, different judgments have been issued for similar disputes.